(untitled) (Research, Society and Development, 2021)
The objective of this work was to analyze the floristic and structural changes of an area with two successional phases in a secondary forest in Capitão Poço - PA. Two measurements were taken with an interval of four years, called Phase 1 and 2. The area has 0.36 ha, divided into 36 subplots of 10m x 10m, where all individuals with DBH ≥ 5 cm were recorded, meeting 444 individuals distributed in 35 species, 26 genera, 19 families with a total basal area of 9,266m2/ha and density of 1,232.33 trees/ha (Phase 1) and 518 individuals distributed in 38 species, 28 genera, 20 families with 11,531m2 /ha of basal area and density of 1,438.89 trees/ha (Phase 2). The species Vismia guianensis, Guatteria amazonica, Lacistema aggregatum and Banara guianensis were the most abundant and frequent. The families with the highest basal area, frequency and IVI were Leguminosae, Clusiaceae, Annonaceae, Lauraceae and Melastomataceae (Phase 1 and 2). The Leguminosae and Clusiaceae families were the most important in the floristic composition and structure of the area, having the highest number of species and individuals, respectively. Therefore, these families must have priority in the silvicultural systems that will be implemented in forests with the same characteristics of the studied area.